Effectiveness and safety of Ayurvedic intervention in essential hypertension: a systematic review with meta-analysis - Deshmukh, Saylee; Choudhary, Kuldeep; Ahmad, Azeem; Reddy, Govind; Rao, B. C. S.; Srikanth, Narayanam; Acharya, Rabinarayan (Frontiers in Pharmacology, 2025)
BackgroundEssential hypertension (EH) is a major contributor to cardiovascular morbidity and mortality that has become a public health challenge owing to poor control and adherence. Many clinical trials have exhibited the effectiveness of Ayurvedic formulations and procedures in the management of EH. In this systematic review and meta-analysis, we present an evaluation of the effectiveness and safety of Ayurvedic interventions compared to conventional therapies for EH.MethodThe systematic review and meta-analysis presented herein adheres to the PRISMA guidelines. Accordingly, we conducted a literature search on PubMed, Cochrane Library, Directory of Open Access Journals, Google Scholar, AYUSH Research Portal, and Ayurveda Research Database for published works up to May 2025. The studies included randomized and non-randomized controlled trials, observational, and pre–post studies of Ayurvedic interventions for EH. The primary outcomes evaluated were systolic and diastolic blood pressure (BP) changes. The risk of bias of ten randomized controlled trials (RCTs) included in the meta-analysis was assessed using the Cochrane guidelines. The meta-analysis was performed in two groups, namely, Ayurveda vs. placebo and Ayurveda vs. standard antihypertensives, using RevMan 5.4.ResultA total of 44 studies was included in the systematic review, and ten RCTs involving 524 participants were included in the meta-analysis. The interventions included single herbs, polyherbal/herbomineral formulations, and panchakarma therapies. Compared to placebo (n = 118), Ayurveda showed a non-significant reduction in systolic BP (mean difference (MD) = −2.63 mmHg; 95% confidence interval (CI): −6.04 to 0.79; p = 0.13) and diastolic BP (MD = −2.67 mmHg; 95% CI: −7.44 to 2.09; p = 0.27). Compared to standard antihypertensives (n = 396), the reductions in systolic BP (MD = −0.22 mmHg; 95% CI: −0.82 to 0.38; p = 0.47) and diastolic BP (MD = −0.66 mmHg; 95% CI: −1.67 to 0.35; p = 0.20) values were non-significant. High heterogeneity (I2 > 90%) was observed during analysis.ConclusionThis systematic review shows that although Ayurvedic interventions do not achieve significant BP reductions versus conventional treatments, they may provide clinical benefits with good safety. The main limitations of the present review are the heterogeneity and methodological differences among the different studies. Hence, high-quality multicenter RCTs with standardized interventions are needed to assess the overall effectiveness of these therapies.Systemetic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42019123886, Identifier PROSPERO.